The Effect of Motivation and Compensation In Improving Employee Performance Mediated By The Organization's Commitment To PT XYZ (A Property Company In Tangerang) - Dyna Fitria; Chandra Wibowo Widhianto (CV. Publikasi Indonesia, 2023)
This study aims to determine the factors that affect employee performance, such as motivation and compensation and the mediating influence of organizational commitment. The sample in this study were employees of Properti company located in the Tangerang area. This research also aims to find out about the turnover phenomenon that occurs at Properti company in Tangerang. The data collection method used a questionnaire and was analyzed using Partial Least Square (PLS). The results of this study will explain whether there is an influence of the factors studied on the high or low quality of Employee Performance experienced by employees working at Properti Company in Tangerang. This study using Motivation and Compensation as Independent variables, Employee Performance as Dependent variables and Organizational Commitment as Intervening variables. In these four variables, seven hypotheses and nineteen indicators were obtained. By using google form media, researchers got 150 respondents. The results of this study indicate that motivation has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, motivation has a positive and significant effect on organizational commitment, compensation has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance mediated by organizational commitment and compensation has a positive and significant effect on employee performance mediated by organizational commitment.